1981
DOI: 10.1177/000331978103200708
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Hospital Stay and Post- Myocardial Infarction Morbidity and Mortality: A Kaiser-Permanente Experience

Abstract: Among 209 evaluable consecutive patients (mean age 57 years) admitted in 1978 and 1979 for acute myocardial infarction, 186 survived. The mean hospital stay of the survivors was 9.7 days. Of these patients, 99 (53%) with complicated myocardial infarction had a mean hospital stay of 11.2 days; 87 (47%) with uncomplicated infarction had a mean stay of 7.9 days. All patients were followed for at least 6 months. During the 6-month post-hospitalization interval, the overall mortality was about 6%. Of the 12 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Whereas the length of stay after uncomplicated STEMI in the United States is approximately 4-5 days, length of stay in complicated STEMI has been shown to average 11 days (36,37). In our study, we demonstrated that patients with clinically diagnosed serious infections had longer length of stay than patients without infections, mirroring previous data on uncomplicated and complicated MIs.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the length of stay after uncomplicated STEMI in the United States is approximately 4-5 days, length of stay in complicated STEMI has been shown to average 11 days (36,37). In our study, we demonstrated that patients with clinically diagnosed serious infections had longer length of stay than patients without infections, mirroring previous data on uncomplicated and complicated MIs.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest proposed discharge-day was day 3,13 but in most studies the patients selected for early discharge could often leave the hospital at day 7,16 8,'14 17, 20,45 9,15 or 10.18 21,41,46,47 This is slightly later than proposed in this study.…”
Section: Circulationmentioning
confidence: 67%